The Effect of Murottal Therapy on Reducing Pain and Anxiety Levels in Post-Surgical Fracture Patients - Amalia Akita; Kalasta Ayunda Putri (Professional Evidence-based Research and Advances in Wellness and Treatment, 2025)
Background: Postoperative pain is one of the main problems experienced by patients after surgery. The use of complementary therapies such as Qur'anic murottal is increasingly being investigated as a nonpharmacological method in pain management. Objectives: This study aims to analyze the effectiveness of Qur'anic murottal therapy in reducing pain scale in postoperative patients with femur fracture. Methods: This study used a quasi-experimental design with a pre-test and post-test approach. The pain scale was measured before and after the murottal therapy intervention given for three consecutive days. Results: The results showed that Qur'anic murottal therapy was effective in reducing pain scale. There was a significant decrease in the pain scale after the intervention, which indicates that this therapy can provide a relaxing effect and increase patient comfort. Conclusion: Qur'anic murottal therapy has the potential to be an effective complementary method in reducing postoperative pain. The application of this therapy may support nonpharmacologic pain management in the medical setting. Further research is needed to confirm these findings in a wider population.